Smart Charger Based on IoT Concept - Muhamad Hilmi Husin; Irfan Danial Hisham (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2019)
This research develops Arduino based smart charging controlling. The aim is to develop a charging that can be controlled by setting the charger in a specific time. Therefore, the problem of overcharging will be anticipated. This research using the AA type of rechargeable battery, Nickel-Metal Hydride (NiMH). C++ is being used for the Arduino. Arduino was chosen for this research because the Arduino boards are able to read inputs – light on a sensor or finger on a button – and turn it into output by activating a motor, turning on an LED, publishing something online. The result of this research is it has succeeded in creating the smart charger that can ensure the safety of the battery by controlling the amount of time in the charging process. The charging will be stopped if the time has reached the limit or if the temperature is high. Indeed, the research will inform the user whether the battery has been full charge or not.